Mihail Posnov – Life and Works - Karavaltchev, Ventslav (Forum Theologicum Sardicense, 2025)
The present study briefly traces the life and creative path of the great theologian M. Posnov, one of the doyens of academic theology in Bulgaria. On the basis of rich sources, his life and academic growth in the former Russian Empire, as well as his life and work in exile are traced. A number of emphases are placed on the difficulties he encounters in the academic circles, which reveals the atmosphere prevailing in these circles during the period under review.